2016
DOI: 10.14411/fp.2016.032
|View full text |Cite
|
Sign up to set email alerts
|

No association between current depression and latent toxoplasmosis in adults

Abstract: Changes in behaviour and cognition have been associated with latent infection from the apicomplexan protozoan Toxoplasma gondii (Nicolle et Manceaux, 1908) in both animal and human studies. Further, neuropsychiatric disorders such as schizophrenia have also been associated with latent toxoplasmosis. Previously, we found no association between T. gondii immunoglobulin G antibody (IgG) seropositivity and depression in human adults between the ages of 20 and 39 years (n = 1 846) in a sample representative of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…However, our results are inconsistent with other studies that found no associations between T. gondii infection and symptoms of depression [14, 23, 2932, 4246]. Many of these studies had limitations in terms of not adjusting for confounders such as occupation, heritability, living environment, cultural practices, socioeconomic status and substance use disorders.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results are inconsistent with other studies that found no associations between T. gondii infection and symptoms of depression [14, 23, 2932, 4246]. Many of these studies had limitations in terms of not adjusting for confounders such as occupation, heritability, living environment, cultural practices, socioeconomic status and substance use disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…Chronic T. gondii infection has also been associated with depression in psychiatric patients [26], women Veterans [27] and pregnant women [28]. However, several other studies found no association between T. gondii infection and depression [23,2932]. One potential source of this discrepancy may be the heterogeneity of samples studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, 9,130 records were excluded through an initial screening of the titles and/or abstracts. The remaining 85 full-text articles were assessed, out of which 27 studies were further compared against our inclusion criteria (Akgül, 2019;Alvarado-Esquivel et al, 2015;Alvarado-Esquivel et al, 2013;Ansari-Lari et al, 2017;Arling et al, 2009;Bak et al, 2018;Burgdorf et al, 2019;Coccaro et al, 2016;Coryell et al, 2016;Dickerson et al, 2018;Dickerson et al, 2017;Ene et al, 2016;Fond et al, 2015;Fond et al, 2018;Gale et al, 2016;Okusaga et al, 2011;Pedersen et al, 2012;Samojlowicz et al, 2013;Samojłowicz et al, 2017;Sapmaz et al, 2019;Sari & Kara, 2019;Sugden et al, 2016;Yagmur et al, 2010;Zhang et al, 2012). Finally, 26 data sets from the 25 records were included in this meta-analysis ( Figure 1).…”
Section: Study Characteristics and Search Resultsmentioning
confidence: 99%
“…Available data suggest that a positive T. gondii antibody titre is probably linked to affective and behavioural changes, as demonstrated in animal and human models (Duffy et al, 2015) (Flegr, 2007;Mann, 2003;Webster, 2001Webster, , 2007. Although some available findings demonstrated a hypothesized relationship between suicide rates and T. gondii infection (Akgül, 2019;Bak et al, 2018;Burgdorf et al, 2019;Pedersen, Mortensen, Norgaard-Pedersen, & Postolache, 2012;Samojłowicz, Borowska-Solonynko, & Kruczyk, 2017;Sapmaz, Şen, Özkan, & Kandemir, 2019;Yagmur, Yazar, Temel, & Cavusoglu, 2010), contradictory results also exist in this regard (Alvarado-Esquivel et al, 2015;Alvarado-Esquivel et al, 2013;Ansari-Lari, Farashbandi, & Mohammadi, 2017;Arling et al, 2009;Coccaro et al, 2016;Coryell et al, 2016;Fond et al, 2015;Fond et al, 2018;Gale, Berrett, Brown, Erickson, & Hedges, 2016;Samojlowicz, Borowska-Solonynko, & Golab, 2013;Sari & Kara, 2019;Sugden et al, 2016;Yolken & Torrey, 2008;Zhang et al, 2012). For SA, we updated the findings of the previous meta-analysis (Sutterland et al, 2019), apart from the inclusion of more databases and articles on SA in an attempt to improve the statistical power to assess the association between T. gondii infection and SA.…”
mentioning
confidence: 99%
“…In a trial using Patient Health Questionnaire Survey data collected by National Health and Nutrition Examination (2009-2012), no association was reported between Toxoplasma-seropositives (13%) and incidence of depression (8%) or suicidal thoughts in the subjects. 40…”
Section: Toxoplasma Mental Disorders and Mind Bugging Sexual Attractionmentioning
confidence: 99%